High-dose influenza vaccine use among patients receiving hemodialysis in the United States, 2010–2013. Issue 41 (1st October 2018) - McGrath, Leah J.; Layton, J. Bradley; Krueger, Whitney S.; Kshirsagar, Abhijit V.; Butler, Anne M.
Abstract: Background: Standard influenza vaccines may be of limited benefit to patients with end-stage renal disease (ESRD). These patients may benefit from high-dose influenza vaccine, currently indicated for patients aged ≥65 years. Studies in other populations have demonstrated that high-dose vaccine elicits a stronger immunological response. We compared vaccine uptake in the United States and predictors of receipt for high-dose and standard influenza vaccines. Methods: Using data from the United States Renal Data System (2010–2013), we conducted a cohort study of 421, 482 adult patients on hemodialysis. We examined temporal trends in uptake of high-dose or standard trivalent influenza vaccine each influenza season, and used multivariate logistic regression to assess the association between individual-level variables (e.g., demographics, comorbidities) and facility-level variables (e.g., facility size and type) with vaccine receipt. Results: The proportion of patients with ESRD who were vaccinated with any influenza vaccine increased from 68.3% in 2010 to 72.4% in 2013. High-dose vaccines were administered to 0.9% of patients during the study period, and 16.7% of high-dose vaccines were administered to patients <65 years of age. Among patients aged ≥65 years, older patients (>79 vs. 65–69 years: OR, 1.29; 95% CI, 1.19–1.41) and patients at hospital-based versus free-standing dialysis facilities (OR, 2.31; 95% CI, 2.13–2.45) were more likely to receive high-dose vaccine, while blacks (vs. whites [OR, 0.66; 95% CI, 0.61–0.71]) and patients with longer duration of ESRD (>9 vs. 0 years: OR, 0.66; 95% CI, 0.55–0.78) were less likely to receive the high-dose vaccine. Conclusions: While the overall influenza vaccination rate has increased, use of high-dose vaccine among patients with ESRD was very low. Being an older patient, living in the Midwest, and receiving care at hospital-based facilities were the strongest predictors of receiving high-dose vaccine.